A one-pot synthesis of 3-trifluoromethyl-2-isoxazolines from trifluoromethyl aldoxime - Gonçalves, Raoni S. B.; Dos Santos, Michael; Bernadat, Guillaume; Bonnet-Delpon, Danièle; Crousse, Benoit (Beilstein Journal of Organic Chemistry, 2013)
Functionalized 3-trifluoromethyl-2-isoxazolines and 3-trifluoromethylisoxazoles were easily prepared from trifluoromethyl aldoxime 2 under mild conditions by using DIB as oxidant. Theoretical studies of the reactivity of trifluoroacetonitrile oxide 4 toward olefins and alkynes were carried out. The 3-trifluoromethyl-2-isoxazolines were ring-opened with NaBH4 and NiCl2 to yield the corresponding trifluoromethylated γ-amino alcohols.
Keywords: aldoxime; amino alcohol; fluorine; isoxazole; isoxazoline; organo-fluorine